Pemberdayaan Kerang Taruna Melalui Pelatihan Teknik Penanaman Hidroponik di Desa Sukoanyar Kecamatan Mojo Kabupaten Kediri - Rhohman, Fatkur; Istiqlaliyah, Hesti; Yasinta Sindy; M. Muslimin Ilham; Nuryosuwito (Jurnal Pengabdian Masyarakat Nusantara, 2021)
Sukoanyar Village is one of the villages located in the southern part of Kediri Regency, Sukoanyar Village is located in Mojo District. Sukoanyar Village Community Most of the residents are farmers, but not all of them have private land, meaning that the majority of them work on other people's gardens, or the "paro" system or better known as the profit sharing system, usually the land owner gets half of the harvest. while those who plant also get half of the harvest. There is one method that can increase farmers' income, namely using a hydroponic system. The application of the hydroponic system is also expected to be a business opportunity for youth members who are currently still entering their productive age. By utilizing the surrounding environment or narrow yard, it can produce plants that can be consumed or sold so as to increase people's income. Hydroponic planting systems can be done with vegetable plants, as well as fruits.